Natural products as pharmacological modulators of mitochondrial dysfunctions for the treatment of diabetes and its complications: An update since 2010 - Qian-Ru Lin; Lian-Qun Jia; Ming Lei; Di Gao; Nan Zhang; Lei Sha; Xu-Han Liu; Yu-Dan Liu (Elsevier, 2024)
Diabetes, characterized as a well-known chronic metabolic syndrome, with its associated complications pose a substantial and escalating health and healthcare challenge on a global scale. Current strategies addressing diabetes are mainly symptomatic and there are fewer available curative pharmaceuticals for diabetic complications. Thus, there is an urgent need to identify novel pharmacological targets and agents. The impaired mitochondria have been associated with the etiology of diabetes and its complications, and the intervention of mitochondrial dysfunction represents an attractive breakthrough point for the treatments of diabetes and its complications. Natural products (NPs), with multicenter characteristics, multi-pharmacological activities and lower toxicity, have been caught attentions as the modulators of mitochondrial functions in the therapeutical filed of diabetes and its complications. This review mainly summarizes the recent progresses on the potential of 39 NPs and 2 plant-extracted mixtures to improve mitochondrial dysfunction against diabetes and its complications. It is expected that this work may be useful to accelerate the development of innovative drugs originated from NPs and improve upcoming therapeutics in diabetes and its complications.